DAYA HAMBAT EKSTRAK RIMPANG BANGLE (Zingiber purpureum Roxb.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - A Citradewi; I M Sumarya; N.K.A. Juliasih (JURNAL WIDYA BIOLOGI, 2019)
The rhizome of the bangle contains antibacterial compounds including saponins, flavonoids, essential oils, and tannins. The aim of the study was to determine the inhibitory power of bangle rhizome extract on the growth of Staphylococcus aureus bacteria. True research - experiment with posttest design with control group was carried out by giving 6 treatment groups, namely negative control group (K-) using aquadest, positive control group (K +) using 30 mcg Chloramphenicol antibiotics, 25% ( PE1), 50% (PE2), 75% (PE3), and 100% (PE4) of concentration of rhizome extract treatment. After the treatment is complete, the inhibition is measured. The research data were analyzed statistically by Kruskall Wallis non parametric test and Sperman Rang correlation test. The results showed that the average inhibition of bangle rhizomes in each group in groups K-, K+, PE1, PE2, PE3, and PE4 were 0.000 ± 0.000, 25.000 ± 0.408, 14.250 ± 0.479, 16.500 ± 0.289, 17.750 ± 0.250, 19,500 ± 0.289 differ significantly (p <0.05). There was a very significant positive correlation between the concentration of rhizome bangle extract and the growth inhibition of Staphylococcus aureus bacteria (r count of 0.967 (**)> r table which was 0.503 at α = 0.05 and n = 24 or p <0.01). Conclusion: bangle rhizome extract at concentrations of 25%, 50%, 75%, and 100% has a strong inhibitory power against the growth of Staphylococcus aureus bacteria. The higher the concentration the greater the inhibitory power.